Problem Based Learning Method with GeoGebra in Mathematical Learning - Ramadhani, Rahmi; Dahlya Narpila, Suci; ., . (International Journal of Engineering and Technology, 2018)
Research objective was to find effect of local culture-problem-based learning method application with used GeoGebra in mathematics learning for senior high school students. Type of this research was quasi-experiment research with post-test only group design. Research sample used three learning class that was chosen by purposive sampling method and was selected from senior high school in Sumatera Utara, Indonesia. Students in experiment-I class was taught with local culture-problem based learning used GeoGebra, students in experiment-II class was taught with problem-based learning and students in control class taught with conventional learning method. Data was analysed with descriptive and inferential through one way-ANAVA test then continued with Tuckey test if data had normal and homogenic distribution, if data had abnormal and/or heterogenic distribution then it was analysed with Kruskal-Wallis test and continued with Mann-Whitney U-Test. Research result showed average value of studentsâ€™ statistical thinking ability test from experiment-I class higher than experiment-II and control class. Based on this research result, then mathematic teachers on senior high school were suggested to applicate local culture-problem based learning with GeoGebra method in mathematics learning and developed mathematic matters which close to studentsâ€™ local culture experience.Â